Analisis Perbandingan Algoritma Lz78 Dengan Algoritma Transformasi Walsh-Hadamard Untuk Kompresi Citra - Alexander Pamdapotan Manullang; Efori Bu’ulolo; Meryance Viorentina Siagian (STMIK Budi Darma, 2022)
Data communication is an activity that is very often carried out in the field of information technology. Data with a large size will take a longer transfer time compared to data that has a smaller size, sometimes there is a risk that it cannot be accommodated on the storage media and is not delivered, so that it will reduce the empty capacity in the memory of the storage media. This can cause the data transformation process to be slow and take a long time. The solution that can solve the above problem is by doing compression. Compression is a technique that can reduce the size of the image to be smaller than its original size. This compression performs a compression technique with compression properties where it is allowed to lose some or most of the data in the image. The algorithm used in this study is the LZ78 algorithm with the Walsah-Hadamard Transform algorithm. To find out the comparison of the compression performance, the parameters to be compared are Ratio of Compression (RC), Space Saving (SS). Based on the results of the researcher's test in comparing the LZ78 algorithm with the Walsh-Hadamard Transformation, the compression value obtained by calculating the ratio that the Walsh-Hadamard Transform algorithm is better than LZ78 where the results of the comparison of the Ratio of Compression of the Walsh-Hadamard Transformation algorithm are 0.71 bits, while the Ratio of 2.66 bit LZ78 compression algorithm. LZ78 62.5% while the Compression Ratio algorithm Walsh-Hadamard Transformation 76%